O direito ao acesso ao tratamento com a toxina botulínica: vozes e vivências dos sujeitos participantes - Gomes, Fábio Alexandre (2010)
This thesis aims to propose and make people consider the experiences of families, participant professionals and users of orthopedic services. All these characters are part of the Association of Support for Children with Orthopedic Disabilities. The central thesis sought to learn the process of fighting for the right of access to treatment with botulinum toxin, which resulted in the implementation of the Reference Center of Botulinum Toxin in São José dos Campos. In this trajectory I have collected information through qualitative research and documentary. In this search I found singular and collective characters and their experiences and narratives, which allowed me to meet their daily realities and meanings attributed by each character, highlighting their political dimension that contributed to the process of guaranteeing the right for treatment experienced by each character. The narratives describe and reflect primarily the care that families have with their children and this generates a concern and commitment in the fight so that their children can enjoy a life trajectory that guarantees them autonomy, which must be experienced in everyday life. We will discuss the obstacles to this population caused by prejudices and difficulties to achieve the realization of basic social rights. We will also present the contribution of professional practice in connection with the characters, establishing a process of reflection of daily life and the construction of citizenship